Analisis Film Perempuan Berkalung Sorban Karya Hanung Bramantyo melalui Model Sara Mills - Andi Yulia Adriani; Abdul Muttalib; Naim Irmayani (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2020)
The background in this study is how the application of Sara Mills's discourse analysis model in the film Perempuan Berkalung Sorban. This study aims to determine how the subject-object position and the position of the reader or audience in the film Woman Berkalung Sorban. The position of the subject is the actor who is the narrator (subject). Meanwhile, the position of the object is who is defined and explained by others (the subject). Meanwhile, the position of the reader is how the reader identifies and places himself in the narrative of the text. This type of research uses descriptive qualitative. The data used in this study are dialogue and image scanning in the film Perempuan Berkalung Sorban. The researchers used the theory of feminism as the basis for Sara Mills's discourse analysis that focused on women. The results of this study conclude, that women who stand alone as feminism are described by the main character Annisa as the owner of a Kyai child from the Salafiah Putri Al-Huda Islamic boarding school and his mother and wife. The women depicted in this film are positioned as intelligent, beautiful, and independent human beings, despite all forms of oppression in the name of gender, and are able to show their dignity and dignity as women. In this film, Berkalung Sorban proves that women are not weak but that men and women are created with the same potential abilities or are usually said with gender equality shown in cut scenes and dialogues in the film.